PENGARUH KOMPETENSI, INDEPENDENSI, DUE PROFESSIONAL CARE, AKUNTABILITAS, DAN ETIKA TERHADAP KUALITAS AUDIT (Studi Empiris pada Auditor Kantor Akuntan Publik di Provinsi Riau dan Kepulauan Riau) - Ayu Ichwanty; Raja Adri Satriawan; Azhari Sofyan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to examine the influence of competency, independency, due professional care, accountability, and ethics to audit quality on Public Accounting Firm (KAP) in Province of Riau and Riau Islands.The population in this study are all auditors who worked at the KAP in Province of Riau and Riau Islands. Sampling was conducted using a simple random sampling method and number of sampling is 40 respondents. The method of data analysis used to test the hypothesis is multiple regression analysis using the program SPSS 20 version.The results of this study proved that competency, independency, due professional care, accountability, and ethics significantly influenced to audit quality. Magnitude of the effect (coefficient determination) caused by competency, independency, due professional care, accountability, and ethics is 52,1% to dependent variable, while the remaining 47,9% is influenced by other variables not examined in this study.Keywords: Competency, Independency, Due Professional Care, Accountability, Ethics, and Audit Quality.